1994
DOI: 10.1139/x94-059
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and biochemical analysis of embryo maturation during yellow cypress seed development

Abstract: Embryo maturation in yellow cypress (Chamaecyparisnootkatensis (D. Don) Spach) seeds was studied at the morphological, anatomical, and biochemical level over the second and third seasons of seed development. Monthly cone collections were made from six open-pollinated families from two seed orchards. The average number of seeds and embryos per cone for each family was 8.8 and 4.6, respectively. Sixty to 70% of those embryos harvested from early collection dates (December 1988–March 1989) were precotyledonary (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…2008); a process that already started prior to fertilisation (Bonner 2008). Further maturation of the seed is accomplished with a certain amount of seed drying (Kurz et al. 1994).…”
Section: Discussionmentioning
confidence: 99%
“…2008); a process that already started prior to fertilisation (Bonner 2008). Further maturation of the seed is accomplished with a certain amount of seed drying (Kurz et al. 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have been carried out on Gymnosperms megagametophyte storage proteins and in conifers they have mainly been based on biochemical characteristics of these proteins (Allona et al, 1994;Kurz et al, 1994;Piovesan et al, 1993). Likewise, our team used these proteins as markers to evaluate the genetic diversity of the stone pine (P. pinea L.), revealing a high level of variation in the studied populations which suggested that this technique could be useful to assess the genetic diversity in conifers (Alvarez et al, 2004).…”
Section: Introductionmentioning
confidence: 97%